ASPECTS OF ISLAMIC CRIMINAL LAW IN REALIZING A CORRUPTION-FREE INDONESIA - Pasyah, Taroman; Nashriana, Nashriana; Ikhsan, Rd. Muhammad; Taslim, Taslim (Tazir, 2025)
As an extraordinary crime, and which can damage the state system, and can endanger the survival and life of the community. Corruption is a complex phenomenon that has a number of causative factors, as reported by the  KPK website there are two factors that cause corruption crimes, namely, internal and external factors. Internal factors are factors that come from oneself. While external factors are factors that come from outside oneself. The rampant criminal act of corruption, with the weak laws and regulations, so that it becomes an entrance for corrupt perpetrators to launch their actions by committing corruption crimes in the country. Even though many efforts have been made by the state, corruption is still increasing both in terms of the quantity of cases and even the quality of corruption crimes that occur tend to be more systematic, more widespread in almost all aspects of people's lives. Departing from the rampant crime of corruption, it is time for the government and law enforcement officials to examine other sources and legal systems in the current national legal system. This research is a normative research that examines the system and sources of law in Islamic law, as a step to realize a corruption-free Indonesia, using the principles of Islamic criminal law.  There are many references that can be used as a reference in efforts to enforce Islamic criminal law in this country, including the prohibition of accepting bribes (riswah), the example of leaders, and the law that is commensurate and mutually supportive and reminding the leaders of the state and the community.